14 National Nutrition survey mapping exercise to explore the association between Vitamin D status and COVID-19. (18th October 2022) - Raja, Nikhita; do Vale, Marjorie Lima; Ray, Sumantra
Abstract : Background: High-risk groups for COVID-19, such as ethnic minorities, also experience the greatest risk for micronutrient deficiencies including Vitamin D. Vitamin D may positively impact COVID-19 prevention and treatment, however, further studies are needed to understand its role. Objectives: To guide further studies exploring Vitamin D and COVID-19, this study aimed to identify national nutrition surveys containing information regarding Vitamin D status, deficiency or supplementation intake. Methods: Systematic searches were performed on MedLine and an extraction template was used to collect information on surveys; country, year of data collection, Vitamin D indicators and access. Results: 27 national nutrition surveys were identified as collecting Vitamin D data across global countries; 8 were publicly available (open-access), 9 required applications and raw-data was not accessible (N/A) for 10. Table 1 displays survey information, including the Vitamin D indicators used. Surveys recorded either serum 25-hydroxyvitamin D (25-OHD) concentration (nmol/L) or estimated Vitamin D intake from interviews/food diaries. Additionally, Vitamin D data was rarely collected in low-income countries such as Africa. Data mapping has outlined disease reporting standards in countries and has emphasised the systematic differences between healthcare systems. Conclusion: Vitamin D data can be combined with COVID-19 incidence and mortality data, to explore the relationship between Vitamin D and COVID-19. Further research can explore inter-individual differences in Vitamin D requirements, optimal therapeutic doses required and how individual requirements can be determined. Findings will improve disease pathway understanding, support the generation of aetiological hypotheses and contribute to COVID-19 prevention and treatment. Substandard diagnosis and reporting in low-middle income countries underestimates disease rates, compared to high income countries. Studies investigating countries across income levels may therefore be affected by case-ascertainment bias, however also highlight where future resources should be directed to improve overall health and reduce inequalities, as well as reducing the burden of COVID-19.